Obesity-induced changes in hepatic and placental clock gene networks in rat pregnancy†. Issue 1 (25th November 2017) - Crew, Rachael C; Waddell, Brendan J; Mark, Peter J
Abstract: Maternal obesity induces pregnancy complications and disturbs fetal development, but the specific mechanisms underlying these outcomes are unclear. Circadian rhythms are implicated in metabolic complications associated with obesity, and maternal metabolic adaptations to pregnancy. Accordingly, obesity-induced circadian dysfunction may drive adverse outcomes in obese pregnancy. This study investigated whether maternal obesity alters the rhythmic expression of clock genes and associated nuclear receptors across maternal, fetal, and placental tissues. Wistar rats were maintained on a cafeteria (CAF) diet prior to and throughout gestation to induce maternal obesity. Maternal and fetal liver and placental labyrinth zone (LZ) were collected at four-hourly time points across days 15–16 and 21–22 of gestation (term = 23 days). Gene expression was analyzed by RT-qPCR. Expression of the accessory clock gene Nr1d1 was rhythmic in the maternal and fetal liver and LZ of chow-fed controls, but in each case CAF feeding reduced peak Nr1d1 expression. Obesity resulted in a phase advance (approx. 1.5 h) in the rhythms of several clock genes and Ppar-delta in maternal liver. Aside from Nr1d1, expression of clock genes was mostly arrhythmic in LZ and fetal liver, and was unaffected by the CAF diet. In conclusion, maternal obesity suppressed Nr1d1 expression across maternal, fetal, and placental compartments and phase-advanced the rhythms of maternal hepatic clock genes. Given the key role of Nr1d1 in regulating metabolic, vascular, and inflammatory processes, our data suggest that disruptions to rhythmic Nr1d1 expression in utero may contribute to programmed health complications in offspring of obese pregnancies. Summary Sentence: Obesity suppresses Nr1d1 expression in maternal, fetal, and placental tissues and phase-advances the rhythms of maternal hepatic clock genes during rat pregnancy.